A new species of Scinax Wagler (Hylidae: Scinaxini) from the tropical forests of Northeastern Brazil - Novaes-E-Fagundes, Gabriel; Araujo-Vieira, Katyuscia; Entiauspe-Neto, Omar M.; Roberto, Igor J.; Orrico, Victor G.d.; Solé, Mirco; Haddad, Célio F.b.; Loebmann, Daniel (Zootaxa, 2021)
We describe a new species of the Scinax ruber clade from Northeastern Brazil that occurs in widely separated geographic areas in the Atlantic Forest of southern Bahia state and the Highland Humid Forest of Serra de Baturité, northeast Ceará state. Scinax tropicalia sp. nov. (holotype coordinates: -14.795694°, -39.172645°) is diagnosed from all 75 currently recognize species of the S. ruber clade by bioacoustical and morphological adult traits, such as duration (0.11–0.31 s) and dominant frequency (1.59–1.85 kHz) of the advertisement call, snout shape rounded, nearly rounded, or semi-circular in dorsal view and rounded to slightly protruding in profile, bilobate vocal sac, absence of pectoral glands and spicule-shaped papillary epidermal projections on nuptial pads, and color pattern on the dorsum of body and hidden surfaces of hindlimbs.